Bahasa inggris - Syahrisal, Syahrisal; Sirman, Mahadir; Habibi, Muhammad; Arjani, Nany; Nur, Rusdi; Nurhidayanti, Nurhidayanti (Politeknik Negeri Ujung Pandang, 2026)
The machining process, especially on a lathe, is greatly influenced by various factors that determine the final surface quality of the workpiece. One of the main factors that influences this quality is the type of cutting tool material and the spindle rotation speed (RPM). This study aims to analyze the effect of variations in the type of cutting tool material and spindle rotation speed on the surface roughness level of the turning results on low-carbon steel materials. The experimental method used is the Taguchi experimental design with an orthogonal approach. L9 array to identify factors that affect the surface quality of machining results efficiently. The independent variables tested were spindle rotation speed at three levels (260, 290, and 450 RPM) and the type of cutting tool material, consisting of three types, namely HSS, Carbide, and Diamond. The results showed that the type of cutting tool material had a more significant effect on surface roughness than the spindle rotation speed. Carbide cutting tools produced the lowest surface roughness, followed by HSS and Diamond. The optimal combination to minimize surface roughness was the use of Carbide cutting tools at a spindle rotation speed of 450 RPM, which produced a surface roughness of about 5.612 µm. Although the linear regression analysis did not show high statistical significance, the model remained diagnostically valid based on the residual test. This study provides an important contribution to the selection of optimal machining parameters to improve the surface quality of turning results in the manufacturing industry.